Pengujian Performa Sistem Informasi Perpustakaan Online Universitas Alma Ata Menggunakan Tools K6 dan GTmetrix - Muhammad Vika Wava Wava; Agung R. Selang; Zavier Zubery (Jurnal Sistem Informasi dan Teknologi Informasi, 2022)
The use of online libraries in universities is very important considering the needs of students in accessing books in online libraries to support lectures. this requires fast and stable performance that can be accessed by all users of the online library, therefore the performance of the online library at Alma Ata University must be a concern because one of the important roles in supporting lectures is testing the system interface to determine the quality both in terms of speed as well as the performance of the online library information system so that it can be used as material for future evaluation. K6 and GTmetrix are the tools used in testing this website. K6 itself is a tool that is often used in load testing, while GTmetrix is ??one of Google's products designed to determine website performance. Testing is done using GTmetrix where this software is designed to be used to measure the performance of a website which will display data that affects the performance of the website being tested.